2019
DOI: 10.36312/jupe.v4i4.674
|View full text |Cite
|
Sign up to set email alerts
|

Minat Partisipasi Dalam Olahraga Ditinjau Dari Suku Bangsa Pada Siswa Di Kota Palangka Raya

Abstract: Aspek psikologi sangat mempengaruhi terhadap kehidupan seseorang dalam menjalankan kehidupan sehari-hari. Salah satu contoh aspek psikologi yang dapat mempengaruhi kehidupan sehari-hari yaitu minat.Sehingga tidak terpisahkan antara aspek psikologi dalamberolahraga.Minat dan partisipasi berolahraga berbeda antara budaya satu dengan yang lainnya. Setiap budaya memiliki norma atau aturan masing-masing yang mengatur kehidupan sosialnya, sehingga akan menciptakan lingkungan dan karakter individu yang berbeda. Hal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…According to sports is an activity that can be done by a person to maintain health and certain other goals. (Harvianto, 2019) When the speaker presented the socialization material, the students seemed enthusiastic about paying attention and listening to the material presented. This can be seen from the active communication between speakers and students when giving material explanations.…”
Section: Implementation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to sports is an activity that can be done by a person to maintain health and certain other goals. (Harvianto, 2019) When the speaker presented the socialization material, the students seemed enthusiastic about paying attention and listening to the material presented. This can be seen from the active communication between speakers and students when giving material explanations.…”
Section: Implementation Methodsmentioning
confidence: 99%
“…This is in line with what was said by the Ministry of Health of the Republic of Indonesia revealed that prevention efforts carried out to break the chain of spread of COVID-19 include socializing the Social Distancing Movement, requiring masks, diligently washing hands using soap or alcohol, and diligently exercising which are all part of clean and healthy living behavior. (Harvianto &;Sakti, 2021) ( Wismanadi et al, 2021) Based on the results of interviews conducted with teachers, the students of SMP Negeri 3 Katingan Tengah are still very minimal in getting education about clean and healthy living behavior. In order to provide solutions to these existing problems, it is necessary to hold an educational activity in the form of socialization about clean and healthy living behavior in the school.…”
Section: Introductionmentioning
confidence: 99%
“…Dalam peningkatan performa atlet guna mencapai prestasi yang ditargetkan, tidak hanya dibutuhkan program latihan secara rutin dan aspek psikologi (Harvianto, 2019), akan tetapi harus juga dibarengi dengan pendukung lainnya. Salah satu pendukung lainnya tersebut yaitu asupan gizi seimbang.…”
Section: Hasil Dan Pembahasanunclassified
“…Meanwhile, according to reference [11] stating that every culture has norms or rules that govern each social life so that it will create an environment and different individual characters. This is what causes individuals to have characteristics that correspond to the culture.…”
Section: B Tribesmentioning
confidence: 99%